Credible Research Designs for Minimum Wage Studies: A Response to Neumark, Salas, and Wascher. (May 2017) - Allegretto, Sylvia; Dube, Arindrajit; Reich, Michael; Zipperer, Ben
The authors assess the critique by Neumark, Salas, and Wascher (2014) of minimum wage studies that found small effects on teen employment. Data from 1979 to 2014 contradict NSW; the authors show that the disemployment suggested by a model assuming parallel trends across U.S. states mostly reflects differential pre-existing trends. A data-driven LASSO procedure that optimally corrects for state trends produces a small employment elasticity (–0.01). Even a highly sparse model rules out substantial disemployment effects, contrary to NSW's claim that the authors discard too much information. Synthetic controls do place more weight on nearby states—confirming the value of regional controls—and generate an elasticity of −0.04. A similar elasticity (−0.06) obtains from a design comparing contiguous border counties, which the authors show to be good controls. NSW's preferred matching estimates mix treatment and control units, obtain poor matches, and find the highest employment declines where the relative minimum wage falls. These findings refute NSW's key claims.